Adverse childhood experiences and food insecurity in emerging adulthood: findings from the EAT 2010-2018 study - Nicole Larson; Susan M Mason; Meg Bruening; Melissa N Laska; Vivienne M Hazzard; Dianne Neumark-Sztainer (Cambridge University Press, 2023)
Abstract Objective: Low childhood socio-economic status (SES) and adverse childhood experiences (ACE) are associated with poor health outcomes in adulthood. Determining how ACE may be linked to food insecurity among young people from socio-economically diverse households can inform health-protective strategies. This study examined if ACE are associated with food insecurity during the transition to adulthood and investigated prevalence differences across SES strata. Setting: Participants were recruited from twenty secondary schools in Minneapolis-St. Paul, Minnesota. Participants: The analytic sample (n 1518) completed classroom surveys in 2009-2010 (mean age = 14·5 years) and follow-up surveys in 2017-2018 (mean age = 22·0 years). Design: Past-year food insecurity was reported at both time points, and ACE were reported at follow-up. Logistic regression models were used to estimate emerging adult food insecurity prevalence by ACE exposure; models were stratified by childhood SES (low, middle and high). Results: The adjusted prevalence of food insecurity was 45·3 % among emerging adults who reported three or more ACE compared with 23·6 % among those with one or two ACE and 15·5 % among those with no ACE (P < 0·001). All forms of ACE were related to an elevated prevalence of food insecurity in emerging adulthood. ACE-food insecurity associations were strongest for emerging adults from lower and middle SES households. Among emerging adults from low SES households, childhood experiences of emotional abuse and substance use by a household member were associated with the largest prevalence differences in food insecurity. Conclusions: Findings suggest a need for trauma-informed services within food assistance programs to better serve individuals with a history of ACE.